Symptomatic Case of Startle Epilepsy with Infantile Brain Damage Treated with Hemispherotomy: A Case Report and Review of Literature - Singh, Yeeshu; Bansal, Atma Ram; Gupta, Aditya; Garg, Arun (Journal of Pediatric Epilepsy, 2016)
We are reporting a case of rare reflex epilepsy—“startle” epilepsy effectively treated with hemispherotomy. A 6-year-old boy, a child of nonconsanguineous parentage with infantile hemiparesis presented to us with recurrent right focal seizures along with secondary generalization provoked by sudden and unexpected auditory stimuli for the last 1 year. The boy had a minimum of four episodes per day despite maximal medical management with multiple antiepileptic drugs. Magnetic resonance imaging of the brain showed severe atrophy of the whole of the left hemisphere. Interictal electroencelphographic (EEG) data showed predominantly left central epileptiform discharges. Long-term video-EEG monitoring record showed seizures of the left hemispheric origin. He underwent a left functional hemispherotomy and has been totally seizure free in the 12-month follow-up period with an improved quality of life both for him and for his caregivers. We feel that surgical management should be considered in startle epilepsy with infantile hemiparesis when seizures are refractory to the optimal medical treatment.
Keywords: startle epilepsy; infantile hemiparesis; hemispherotomy